OBSERVATIONS ON A NEW EPIDEMICAL EYE DISEASE AFFECTING THE INDIAN CARP CATLA CATLA (HAMILTON BUCHANAN) - Gopalakrishnan, V (Indian Journal of Fisheries, 2011)
Catla catla is one of the major carps extensively cultured in West Bengal andadjoining States of India. During the last quarter of 1959, many unusualcases of fish mortality were observed in several districts of West Bengal andpreliminary investigations indicated that the fish had died due to widespreadoccurrence of a new type of eye disease, the infection being confined to Catlacatla (Gopalakrishnan and Gupta, 1960). Spot surveys made at Barrackpore,Nilganj and Naihati indicated that many fish were affected by the diseaseand that the damage caused was considerable, about eleven metric tonnes offish having perished during two months in these areas alone. Subsequentreports about the same disease were received from other areas like Chandernagore,Midnapore and Kancharapara also. Exact mortality figures werealways not available because the fishery owners were anxious to sell off theirstocks without disclosing the presence of the disease conditions, lest the fishmight become either unsaleable or fetch very low prices. The epidemic wasprevalent during October-January, 1959-60, and appeared again duringthe last quarter of the latter year.